Pengungkapan Sustainability Reporting, Intellectual Capital, dan Nilai Perusahaan pada Perusahaan Pertambangan - Karya, I Made Adi Saputra; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2023)
The research aims to obtain empirical evidence regarding the disclosure of Sustainability Reporting and Intellectual Capital on company value in the mining industry. This research was conducted at mining companies listed on the Indonesia Stock Exchange for the period 2016 to 2019. The sampling technique used was purposive sampling with a total of 32 observations during the study period. The data analysis technique used is multiple regression analysis. This study shows that Sustainability Reporting has a significant negative effect on firm value, while Intellectual Capital has a significant positive effect on firm value. Keywords : Company Value; Intellectual Capital; Sustainability Reporting.